The Influence of Psychological Safety towards Employee Engagement Using Organizational Support as Intervening Variable - Jesica Vionica Wowor; Yustina Ertie Pravitasmara Dewi (Management Institute Faculty of Economics Universitas Andalas, 2022)
Psychological safety creates a safe and convenient environment for employees which can be seen by daring to take risks. Employee engagement can retain employees in their jobs so that physical, cognitive, and emotional involvement exists. When employees feel supported and valued, they are comfortable staying in their job. This study explores the influence of psychological safety on employee engagement with organization support as an intervening variable. This study was conducted on Generation Z employees in Central Java with a total of 155 employees. The analytical technique used is regression analysis. From the study result, psychological safety influences employee engagement significantly, and psychological safety also significantly influences perceived organization support. Meanwhile perceived organization support variable is not proven to mediate the effect of psychological safety on employee engagement.